Politics and religion in the White South - Feldman, Glenn (Religion in the South., 2005)
Politics and Religion in the White South examines the powerful ways in which religious considerations have shaped American political discourse. Since the inception of the Republic, politics have remained a subject of lively discussion and debate. Although based on secular ideals, American government and politics have often been peppered with Christian influences. Especially in the mostly Protestant South, religion and politics have been nearly inextricable. This collection of thirteen essays from prominent historians and political scientists, including Mark K. Bauman, Charles S. Bullock III.